ANALISIS KENDALA IMPLEMENTASI P5 DALAM KURIKULUM MERDEKA DI UPT SDN 013 GANTING - Nurazlina; Mufarizuddin; Rizki Ananda; Hannisa Haris; M. Syahrul Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Merdeka Curriculum through the Pancasila Student Profile Strengthening Project (P5) aims to holistically shape students’ character; however, its field implementation still faces various challenges. This study aims to describe teachers’ understanding of the P5 concept, identify implementation barriers, and outline school strategies to overcome them. A descriptive qualitative method was employed, with data collected through observation, in-depth interviews, and documentation. The findings indicate that teachers view P5 as an integral part of character education, yet most still require technical training for optimal implementation. Identified obstacles include limited infrastructure, low engagement from some teachers, and insufficient active participation from parents. The school’s strategies involve developing detailed modules, conducting internal training, and collaborating with external parties. The study concludes that successful P5 implementation requires full teacher commitment and adequate facilities. These findings are expected to serve as a reference for policymakers and schools in improving the quality of P5 implementation.